IMPLEMENTASI MANAJEMEN KEAMANAN INFORMASI BERBASIS ISO 27001 PADA SISTEM INFORMASI AKADEMIK - Intan Mafiana, Agnes; Hanum, Luthfiah; Ilmi, Hanifah Mufidatul; Febriliani, Silvani (Journal of Digital Business and Innovation Management, 2023)
The implementation of data security in academic systems is crucial to protect highly sensitive student, faculty, and administrative information. The ISO 27001 standard has become a critical guide in the development and implementation of effective information security measures. This research aims to evaluate the use of ISO 27001 in the context of Universitas Negeri Surabaya (Unesa) and analyze its impact on data security in the academic environment. The research identified risks relevant to Unesa’s academic systems, including cyber threats and physical risks. The results of this study confirm that the implementation of ISO 27001 has had a positive impact on data security at Unesa. The implementation of appropriate security controls and effective risk reduction has assisted in maintaining the integrity of academic data and protecting valuable information assets. As such, Unesa students, lecturers and administrative staff feel more confident that their data is safe and secure. This research provides important insights into the key role played by the ISO 27001 standard in securing academic systems in higher education institutions. It also underscores the importance of continuous risk evaluation, implementation of appropriate controls, and regular security monitoring as part of a successful data security strategy.